Paired Combinations in Kazakh Language and it´s Ways of Translation into Russian - ISKHAKOVA, Gulnaz Renatovna; KIRILLOVA, Zoya Nikolaevna; YERBULATOVA, Ilmira Kanatovna (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article is dedicated to the study of the lexical category of the pairs of words represented by the copulative addition containing the specific national-cultural meaning. The purpose of this article is to define such concepts as paired combinations, copulative additions, paired-compound utterances, binomials, syntagma formula, reduplications, tautological phraseological units, paratactic combinations. The main results of the study make it possible to find out how the typical tasks of the literary translation of the considered category of pair words are realized to recreate the specific national and cultural background of the Kazakh language metaphysics. RESUMEN Este artículo está dedicado al estudio de la categoría léxica de los pares de palabras representadas por la adición copulativa que contienen el significado nacional-cultural específico. El propósito de este artículo es definir conceptos tales como combinaciones pareadas, adiciones copulativas, expresiones compuestas pareadas, binomios, fórmulas de sintagma, reduplicaciones, unidades fraseológicas tautológicas, combinaciones paratácticas. Los principales resultados del estudio permiten descubrir cómo se realizan las tareas típicas de la traducción literaria de la categoría considerada de palabras en pares, para recrear los antecedentes nacionales y culturales específicos de la metafísica del idioma kazajo.